MANIFESTATIONS OF EXCESSIVE DAYTIME SLEEPINESS AND GHRELIN LEVEL IN CASE OF GASTROESOPHAGEAL REFLUX DISEASE IN PATIENTS WITH UNDIFFERENTIATED CONNECTIVE TISSUE DISEASE - Romash, Iryna B; Mishchuk, Vasyl H; Romash, Ivan R; Krasilych, Iryna O; Romash, Nadiya I; Vus, Viktor I; Kolinko, Yaroslav (Wiadomosci lekarskie (Warsaw, Poland, 2022)
OBJECTIVE: The aim of the study was to discover the interrelation between the severity of gastroesophageal reflux disease (GERD) symptoms, acid exposure time (AET), excessive daytime sleepiness (EDS) and the level of active blood plasma ghrelin in the patients with undifferentiated connective tissue disease (UCTD). PATIENTS AND METHODS: Materials and methods: The study included 120 patients with GERD. All the patients were divided in two groups: Group I - GERD was not accompanied by the signs of connective tissue disease (n=45) and Group II - GERD developed on the background of UCTD syndrome (n=75). Daily transnasal pH monitoring was performed to determine the nature of pathological refluxes. EDS was detected by The Epworth Sleepiness Scale. Active ghrelin in blood plasma samples was determined by ELISA. RESULTS: Results: 80% of the patients of Group II and 35.48% of Group I suffered from EDS (p<0.05). The mean daily AET index was 5.48±0.4% in Group II and 6±0.2% in Group I, in the night hours mostly when patients were in the upright position. This phenomenon contributed to a deterioration of sleep quality and the appearance of EDS and was supported by a connection between AET and EDS (r=+0.827 for Group I and r=+0.768 for Group II). The mean De Meester index was higher in the patients of Group II (23.01±2.24 in Group I vs 31.08±2.4 in Group II; p<0.05). CONCLUSION: Conclusions: GERD manifestations are strongly related to the level to AET and intensity of EDS. The EDS symptoms depend on circulating ghrelin level.
Keywords: Ghrelin; nediferencované onemocnění pojivové tkáně; undifferentiated connective tissue disease; excessive daytime sleepiness; Gastroesophageal Reflux; lidé; poruchy nadměrné spavosti; ghrelin; gastroezofageální reflux; Disorders of Excessive Somnolence; Undifferentiated Connective Tissue Diseases; gastroesophageal reflux disease; Humans